Macromedia Flash Animation Media in Science Learning Based on the Direct Instruction Model on ecosystem component material in Elementary Schools - Ade Islamiati; Yanti Fitria (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The current demands of the 2013 curriculum, especially in science learning, require students to be active in learning. But in reality, when the learning process is taking place, it can be seen that learning is presented as teacher-centered. The aim of the research that researchers hope is to increase the participation and ability of students to explore and solve problems given during the learning process. Direct Instruction Model (Direct Instruction) is a learning model where the teacher does not play a role in delivering the material but the teacher helps students to be able to explore their basic skills and is able to find information that has been given by the teacher step by step. The use of Macromedia Flash in learning will attract the attention of students because Macromedia Flash is designed to create motion or animation media that will attract the attention of students. From the results of the research that the researchers have done, it was found that students were very active and enthusiastic during the learning process as evidenced by the high level of participation and students' understanding of the material presented. From the results of the research that the researchers have done, it has been seen that by using the Direct Instruction Model with the help of Macromedia Flash in science learning, ecosystem component materials are able to increase the activity, participation and ability of students to solve the problems given.